Towards Educational Systems-of-Information Systems: Reporting Results of an Exploratory Study - Neves, Vânia de Oliveira; Garcés, Lina; Graciano, Valdemar (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Virtual Learning Environments (VLE), such as Moodle and Canvas, are often used in online learning to support both classroom and semi-classroom courses. Considering the abundance of VLE and the different functionalities offered by them, teachers/professors (and students, as a consequence) are often required to use multiple tools at the same time to fulfill all the objectives of their courses. Hence, it is necessary to excessive time and effort for VLE management (on the teachers’ side), leading to difficulties and misunderstanding for the students. Currently, VLEs are independent, highly-coupled, built with different technologies, and supported by various organizations. Moreover, VLEs offer specific functionalities that, frequently, must be complemented with other technologies to provide more complete solutions. In this perspective, VLEs present characteristics of System-of-Systems (SoS), i.e., large software systems whose operations depend on the collaboration and interactions between individual systems that are managerial and operational independent. This work presents preliminary results of constructing Educa-SoIS, an Educational Systems-of-Information-Systems that combines the individual capabilities of several VLEs in a single system offering a more complete solution to teachers and students. We describe the Educa-SoIS missions (i.e., high-level objectives that this educational SoIS needs to achieve), the types of independent systems (existing VLEs) that can compose the Educa-SoIS , the Educa-SoIS architecture, as well as an implementation of this architecture. Preliminary results reveal (i) a demand for this type of system, (ii) the feasibility of its existence, and (iii) the need for further investigation.